An analysis of themes from dissertations defended in the research line of teaching training and pedagogical practices in professional education of PPGEP/IFRN (2015 – 2016) (Revista Internacional de Formação de Professores, 2019)
This article analyzes the dissertations defended in the Postgraduate Program in Professional Education PPGEP – IFRN. To discuss the thematic approaches of the investigations carried out in the line of research: Teacher Training and Pedagogical Practices. The dissertations defended were analized the in the period between June 2015 and December 2016, referring to this line. The results show 12 productions that meet the descriptors of the above research line. It is considered that the production analyzed reflects how the implementation of this Program has taken place by the specific approaches of already developed researches that bring discussions about: teacher training processes and pedagogical practices developed in professional education field.
Keywords: Research in Professional Education. Academic production. Masters dissertation. Teacher Training and Pedagogical Practices.